The power and promise of genetic mapping from Plasmodium falciparum crosses utilizing human liver-chimeric mice - Katrina A. Button-Simons (Nature Portfolio, 2021)
Button-Simons et al. report on two different genetic crosses of Plasmodium falciparum derived from Asian and African origin parasites, and generate large numbers of recombinant progeny. These crosses are characterized and have the potential to map biologically important traits across parasite genomes.